Risk of dyslipidemia and major adverse cardiac events with tofacitinib versus adalimumab in rheumatoid arthritis: a real-world cohort study from 7580 patients - Ma, Xiao-Na; Shi, Mei-Feng; Wang, Shiow-Ing; Feng, Wei; Chen, Shu-Lin; Zhong, Xiao-Qin; Liu, Qing-Ping; Cheng-Chung Wei, James; Lin, Chang-Song; Xu, Qiang (Frontiers in Pharmacology, 2024)
Objective: To compare the effects of tofacitinib and adalimumab on the risk of adverse lipidaemia outcomes in patients with newly diagnosed rheumatoid arthritis (RA). Methods: Data of adult patients newly diagnosed with RA who were treated with tofacitinib or adalimumab at least twice during a 3-year period from 1 January 2018 to 31 December 2020, were enrolled in the TriNetX US Collaborative Network. Patient demographics, comorbidities, medications, and laboratory data were matched by propensity score at baseline. Outcome measurements include incidental risk of dyslipidemia, major adverse cardiac events (MACE) and all-cause mortality. Results: A total of 7580 newly diagnosed patients with RA (1998 receiving tofacitinib, 5582 receiving adalimumab) were screened. After propensity score matching, the risk of dyslipidaemia outcomes were higher in the tofacitinib cohort, compared with adalimumab cohort (hazard ratio [HR] with 95% confidence interval [CI], 1.250 [1.076-1.453]). However, there is no statistically significant differences between two cohorts on MACE (HR, 0.995 [0.760-1.303]) and all-cause mortality (HR, 1.402 [0.887-2.215]). Conclusions: Tofacitinib use in patients with RA may increase the risk of dyslipidaemia to some extent compared to adalimumab. However, there is no differences on MACE and all-cause mortality.